A Study on Nexus Between Renewable Energy and Fossil Fuel Consumption in Commercial Sectors of United States Using Wavelet Coherence and Quantile-on-Quantile Regression - Singh, Sanjeet; Bansal, Pooja; Bhardwaj, Nav (Frontiers in Energy Research, 2022)
The inertia of fossil fuels in the commercial sector in the US has maintained its momentum throughout. Efforts to replace it with renewable energy have continually been made. This is dynamic relationship is impacted by multi economic and political variables both in the domestic and international markets. While factors such as global warming and air pollution impact the government policy for renewable energy and fossil fuels alike, certain variables such as crude oil prices, industrial production, etc, impact the two variables individually. In this paper, we try to evaluate the connection between the total Renewable Energy consumption (RE) and the energy consumed by Fossil Fuels in the commercial sector (FE) in the USA using Wavelet coherence and Quantile on quantile regression (QQR) techniques. To assess this, we have procured monthly data from the US energy information Administration over the period of Jan – 2001 to July – 2021. We find that in four out of the five models assessed, Renewable Energy consumption has an antagonistic relationship with the energy consumed by Fossil Fuels in the commercial sector in the US. Using the wavelet coherence, a huge island of significant coherence is observed in a few frequency bands indicating a long-term impact with variables being out-phase indicating a negative correlation.